The influence of Zn2+ ions on the local structure and thermochromic properties of Cu1-xZnxMoO4 solid solutions - Pudza, Inga; Anspoks, Andris; Cintins, Arturs; Kalinko, Aleksandr; Welter, Edmund; Kuzmin, Alexei (Elsevier, 2021)
The influence of zinc ions on the thermochromic properties of polycrystalline CuZnMoO (=0.10, 0.50, 0.90) solid solutions was studied by X-ray absorption spectroscopy at the Cu, Zn and Mo K-edges. Detailed structural information on the local environment of metal ions was obtained from the simultaneous analysis of EXAFS spectra measured at three metal absorption edges using the reverse Monte Carlo method. Thermochromic phase transition with the hysteretic behaviour between and phases was observed in Cu0.90Zn0.10MoO solid solution. It was found that the local environment of molybdenum ions is most susceptible to the substitution of copper for zinc and, upon cooling, transforms from tetrahedral MoO to distorted octahedral MoO. ---- / / / ---- This is the preprint version of the following article:Inga Pudza, Andris Anspoks, Arturs Cintins, Aleksandr Kalinko, Edmund Welter, Alexei Kuzmin, The influence of Zn2+ ions on the local structure and thermochromic properties of Cu1-xZnxMoO4 solid solutions, Materials Today Communications, Volume 28 (2021), 102607, DOI https://doi.org/10.1016/j.mtcomm.2021.102607, which has been published in final form at https://www.sciencedirect.com/science/article/abs/pii/S2352492821005997.
I. P., A. K. and A. K. would like to thank the support of the Latvian Council of Science project No. lzp-2019/1-0071. I.P. acknowledges the L‘OREAL Baltic “For Women In Science” Program with the support of the Latvian National Commission for UNESCO and the Latvian Academy of Sciences. The experiment at the PETRA III synchrotron was performed within project No. I-20190277 EC. The synchrotron experiments have been supported by the project CALIPSOplus under the Grant Agreement 730872 from the EU Framework Programme for Research and Innovation HORIZON 2020. Institute of Solid State Physics, University of Latvia as the Center of Excellence has received funding from the European Union’s Horizon 2020 Framework Programme H2020-WIDESPREAD-01-2016-2017-TeamingPhase2 under grant agreement No. 739508, project CAMART2.
Keywords: Research Subject Categories::NATURAL SCIENCES:Physics; Cu1-xZnxMoO4; Solid solutions; Thermochromism; EXAFS; XANES